Effect of Destination Image and Subjective Norm toward Intention to Visit the World Best Halal Tourism Destination of Lombok Island in Indonesia - Aulia Ramadhani, Sintesa; Kurniawati, Masmira; Hadi Nata, Jiwangga (KnE Social Sciences, 2020)
One of the halal attractions in Indonesia is Lombok Island, which was ranked as the Best Halal Travel Destination in Indonesia according to the IMTI 2018 and was also named the best halal destination in the international arena in tourism, at the World Halal Travel Summit 2015. In fact, Lombok managed to win two titles at once, namely as the World’s Best Honeymoon Destination and the World’s Best Halal Tourism Destination. Besides being known as the island of 1000 mosques, Lombok also provides easy access to buy halal food, easy access to Shariah hotels, to make rules for visiting Shariah beaches, and religious communities. Using Lombok as a prime example, this study seeks to identify what Islamic tourists want in a tourist site. By looking at the various achievements of the Lombok Island, the researchers are willing to find out the causes of tourists visiting the Lombok Island. In particular, this study aims to determine the effect of destination image and subjective norms on the intention to visit Lombok Island. This paper is based on 100 respondents (each of whom was at least 17 years old and had never visited a halal destination in Lombok). This study uses SPSS 22. The results of the study concluded that destination image and subjective norms had a significant influence on intention to visit halal destination in Lombok Island. Keywords: Image Destination; Subjective Norm; iIntention to Visit